Koincidence lokalizace defektů vrstvy junkce IS/OS fotoreceptorů na SD OCT s funkcními poruchami v prípade Stargardtovy choroby - Rencová, E; Studnicka, J; Marák, J; Dvoráková, H; Langrová, H (Ceska a slovenska oftalmologie, 2012)
Case report of the different visual functions of the right and left eye of 60-years old man with Stargardt disease is presented. The difference in best corrected visual acuity between both eyes is accompanied with corresponding various alteration of the central retinal activity using multifocal electroretinography (mfERG) and asymmetrical defects of the IS/OS photoreceptor junction using HD-OCT.
Keywords: elektroretinografie; optická koherentní tomografie; Tomography, Optical Coherence; retinální dystrofie; Humans; mužské pohlaví; Male; fotoreceptory obratlovců; lidé; lidé středního věku; Electroretinography; Middle Aged; Photoreceptor Cells, Vertebrate; zraková ostrost; Retinal Dystrophies; Visual Acuity